Holographic tests for giant graviton expansion - Seunggyu Kim; Eunwoo Lee (Journal of High Energy Physics)
Abstract It has been proposed that the superconformal index admits a novel reformulation, called giant graviton expansion. In this paper, we investigate the properties of dual AdS 5 black holes using the giant graviton expansion framework. First, we compute the entropy of black holes in AdS 5 × S 5 with fixed charges through a large N saddle point analysis on the ‘giant graviton index’. In addition, we show that the giant graviton expansion of the index provides a natural way to understand how small black holes in AdS can be viewed as bound states of branes. We extend our study to include the giant graviton expansion with the insertion of a half-BPS surface defect in N $$ \mathcal{N} $$ = 4 SYM with a U(N) gauge group. Finally, we test the giant graviton expansion in various holographic theories whose dual geometries are AdS 5 × S 5/ℤ k and AdS 5 × SE 5.